Analysis of the Comprehensive Power of Grenade Simulation Ammunition - PEI Guiyan, NIE Jianxin, WANG Qiushi, JIAO Qingjie (Zhihui kongzhi yu fangzhen, 2023)
As one of the main ammunitions for attacking air targets, the fragmentation and shock wave power of grenades are important parts of evaluating damage ability. In order to study the comprehensive power of grenade, grenade simulation ammunition is designed refers to Italy’s Oto Melera 127 mm ammunition. On the basis of experiment, numerical simulation and empirical formula, the fragmentation velocity, fragmentation spatial distribution and shock wave overpressure are analyzed. The experimental results show that,the scattering direction angle of the grenade simulation ammunition is 93.67°, the scattering angle is 65.42°, and the initial velocity of the fragments is 1 451 m/s. The simulation and calculation results show that, for the scattering angle, the deviation between theoretical and experimental values is relatively small, for fragmentation velocity, the error between theoretical calculation and experimental value is less than 20%, for shock wave overpressure, the error of theoretical value, simulation value and experimental value is less than 15%.